Inteligência artificial e racionalidade instrumental: implicações do ChatGPT nos processos educativos - Melo, Michele Carolina de Jesus (2025)
This master’s research, developed in the Graduate Program in Education at the Federal University of Goiás (PPGE/UFG) and situated within the research line of Educational Process Fundamentals, focuses on analyzing the growing use of artificial intelligence, particularly ChatGPT, in educational processes. The main objective of the study is to analyze the implications of using ChatGPT as a mediator in knowledge production and its consequences for the constitution of individuals. The study also aims to analyze the connections between the development of the tool and instrumental rationality, which is objectively produced by the capitalist mode of production, as well as the updates of pseudo-formative processes in contemporary society. Therefore, this research involves the analysis of a subject supported by the theoretical foundations of Critical Social Theory. The main references are Adorno (1959/2010), Adorno and Horkheimer (1947/1985), Horkheimer (1947/2015), and Marx (1867/2023). The fact that ChatGPT has developed and gained popularity as the primary "solution" to knowledge production needs, within the range of tools based on artificial intelligence development, is something that deserves further exploration and a more detailed view. This is because the tool appropriates intellectual labor historically produced and presents this "knowledge" as ready-to-use information to individuals, under the illusion of authorship. In this process, there is a predominance of intellectual economy among the users of the tool, implying an ephemeral experience with strictly pragmatic meaning. Thus, this research object problematizes the already announced disharmony between the development of artificial intelligence and the principles of humanization. From the study conducted, it was possible to observe some emerging trends in this particular historical moment, updated through the relationship of individuals with ChatGPT. Among them are: the expropriation of authorship, as the production generated by the tool is done by an intelligence that is not the user's own, depriving the individual of creativity, autonomy, and therefore authorship; the existence of a productivity-driven logic, intrinsic to capitalist rationality, which imposes constant pressure on individuals to optimize their time and increase productivity, constituting them to relentlessly seek immediate results at the expense of process and reflection; the abandonment of developing certain human capacities, such as concentration and focus; the decline in reading ability; as well as an intensification of the process of capital valorization and the deepening of labor devaluation due to the advent of generative artificial intelligence. To analyze the reconfiguration of the world of work through AI, this research draws on the Marxian category of machinery, questioning whether this category is still explanatory of reality. Thus, the main contribution of the research is to reveal that ChatGPT is produced within the logic of instrumental rationality and, when used as a mediating tool for knowledge production, contributes to the (de)formation of individuals, reaffirming reification and dehumanization as a historical trend.